Corporate Social Responsibility and Firm Performance in SMEs: Empirical Evidence from Cameroon - Ramecesse, Ateufack Djogho (Business and Economic Research, 2021)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">We examined the mediating effects of corporate governance and image on CSR and performance link. We find CSR positive related to firm performance but insignificant. We further established CSR and FP are positive and insignificant without the existence of CI and CG but becomes significant with the inclusion of both mediating variables. Therefore, corporate governance codes and principles should be enhanced in Cameroon, since CSR engagement helps in better governance practice through establishing good internal controls and monitoring that ultimately enhances a firm financial performance. Several policy recommendations were discussed.